2022
DOI: 10.1016/j.vaccine.2021.12.036
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine is correlated with favourable epidemiological indicators in the Auvergne-Rhône-Alpes region (France): An ecological study

Abstract: COVID-19 vaccination has proven to be effective in preventing severe cases, reducing viral load, and transmissibility. The aim of this study was to evaluate the impact of vaccination 11 months after implementation on epidemiological indicators and the effective reproduction number in one French region. We plotted four indicators with vaccination coverage as the explaining variable and estimated the impact of vaccination using the reduction rates in infections and hospital admissions. A reduction of 98% in COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This finding is in line with data from Brazil, where an important decline in mortality in adults aged ≥80 years was seen after the introduction of the COVID-19 vaccine ( 25 ). Studies in Canada, France, and Israel also showed that initial vaccination efforts directed at adults aged 65 years and older resulted in significant overall declines in COVID-19 cases and deaths, ranging from 21% to 80% in COVID-19 cases and 30% to 87% in COVID-19 deaths ( 10 , 26 , 27 ). Given the greater COVID-19 vaccine efficacy against hospitalization and death, further studies to evaluate the effect of COVID-19 vaccines on different clinical outcomes, such as mortality or hospitalization, in the general population would be useful to increase the evidence of the public health benefits of COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with data from Brazil, where an important decline in mortality in adults aged ≥80 years was seen after the introduction of the COVID-19 vaccine ( 25 ). Studies in Canada, France, and Israel also showed that initial vaccination efforts directed at adults aged 65 years and older resulted in significant overall declines in COVID-19 cases and deaths, ranging from 21% to 80% in COVID-19 cases and 30% to 87% in COVID-19 deaths ( 10 , 26 , 27 ). Given the greater COVID-19 vaccine efficacy against hospitalization and death, further studies to evaluate the effect of COVID-19 vaccines on different clinical outcomes, such as mortality or hospitalization, in the general population would be useful to increase the evidence of the public health benefits of COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%